Disrupted balance of T cells under natalizumab treatment in multiple sclerosis. Issue 2 (April 2016) - Kimura, Kimitoshi; Nakamura, Masakazu; Sato, Wakiro; Okamoto, Tomoko; Araki, Manabu; Lin, Youwei; Murata, Miho; Takahashi, Ryosuke; Yamamura, Takashi
Abstract : Objective: To compare effects of natalizumab on inflammatory and regulatory T cells with regard to expression of α4-integrin (CD49d). Methods: Twenty-seven natalizumab-naive and 8 natalizumab-treated patients with multiple sclerosis (MS), 7 patients with neuromyelitis optica (NMO) or NMO spectrum disorder, and 8 healthy controls were included. The positive rate of CD49d was analyzed and compared among T helper 1 (Th1), T helper 17 (Th17), and regulatory T (Treg) cells (CD49d+Th1, CD49d+Th17, and CD49d+Treg, respectively). Results: Natalizumab treatment increased CD49d ratios, CD49d+Th1/CD49d+Treg, and CD49d+Th17/CD49d+Treg. This indicates larger reduction of the CD49d+ population in Treg cells than in Th1 or Th17 cells. The CD49d ratios of 2 patients who experienced exacerbation during natalizumab treatment were remarkably higher than those of the other natalizumab-treated patients. Natalizumab treatment increased the expression of TBX21, RORC, interferon (IFN)–γ, and interleukin (IL)–17A, and decreased the expression of FOXP3 in CD49d+ memory CD4 T cells. Natalizumab treatment also increased the amount of IFN-γ and IL-17A secreted by CD49d+ memory CD4 T cells. Conclusions: The reduction rate of the CD49d+ population in Treg cells was larger than that in Th1 or Th17 cells. Although the large reduction in CD49d+ population is beneficial for MS, the proinflammatory state of residual CD49d+ cells might, in part, explain the presence of disease activity under natalizumab treatment.